2021
DOI: 10.1080/19490976.2021.1884517
|View full text |Cite
|
Sign up to set email alerts
|

YjbH mediates the oxidative stress response and infection by regulating SpxA1 and the phosphoenolpyruvate-carbohydrate phosphotransferase system (PTS) in Listeria monocytogenes

Abstract: Song (2021) YjbH mediates the oxidative stress response and infection by regulating SpxA1 and the phosphoenolpyruvate-carbohydrate phosphotransferase system (PTS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that, under butanol stress, the transcription of PTS genes transporting mannitol and cellobiose in L. plantarum WCFS1 is downregulated [68]. It has been reported that, under oxidative stress, the expression of multiple PTS genes in Listeria monocytogenes YjbH is downregulated, and the degree of downregulation is as great as hundreds of times the normal amount [69]. In addition, transport proteins are important osmoregulators that are responsible for the uptake and excretion of vital substances such as inorganic ions, sugars, and amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, under butanol stress, the transcription of PTS genes transporting mannitol and cellobiose in L. plantarum WCFS1 is downregulated [68]. It has been reported that, under oxidative stress, the expression of multiple PTS genes in Listeria monocytogenes YjbH is downregulated, and the degree of downregulation is as great as hundreds of times the normal amount [69]. In addition, transport proteins are important osmoregulators that are responsible for the uptake and excretion of vital substances such as inorganic ions, sugars, and amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Lmo0964, namely YjbH, was first demonstrated to be necessary for ActA translation ( 26 ). Further reports have clarified that YjbH directly interacts with SpxA1 and plays a pivotal role in bacterial adaption to oxidative stress and host infection ( 27 , 28 ). Here, we aimed to investigate the biological roles of Lmo1059 in oxidative stress tolerance and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of L. monocytogenes gene deletion mutants was performed as described previously ( 27 ). The temperature-sensitive pKSV7 shuttle vector generated mutations in the L. monocytogenes strain EGD-e. A homologous recombination strategy with the splicing by overlap extension (SOE) PCR procedure was used for in-frame deletion to construct gene deletion mutants.…”
Section: Methodsmentioning
confidence: 99%
“…The migration distance around the incubation site was also measured. The migration distance was found to be directly proportional to the motility ability ( 52 , 53 ).…”
Section: Methodsmentioning
confidence: 99%